PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI SEKRETARIAT DAERAH KOTA PADANG - Syaiful Andri; Yunia Wardi (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
The purpose of this study was to analyze : 1 ) The effect of leadership on organizational commitment Padang Regional Secretariat . 2 ) The effect of work motivation on organizational commitment Padang Regional Secretariat . 3 ) The effect of leadership on job satisfaction of the Regional Secretariat staff Padang . 4 ) The effect of work motivation on employee job satisfaction Regional Secretariat of Padang . 5 ) The effect of organizational commitment on job satisfaction of the Regional Secretariat staff Padang. This type of research is the study of causality . The population in this study were all within the Regional Secretariat Employees Padang , amounting to 226 people . The sample size is 144 employees . The technique of data analysis is descriptive analysis , test analysis and hypothesis testing requirements with path analysis. The results of this study found that : 1 ) Leadership significant effect on the organizational commitment of employees of the Regional Secretariat of Padang. 2 )Work motivation significant effect on the organizational commitment of employees of the Regional Secretariat of Padang. 3 ) Leadership significant effect on employee job satisfaction Regional Secretariat of Padang. 4 )Work motivation significant effect on employee job satisfaction Regional Secretariat of Padang. 5 ) significantly influence the organizational commitment to employee satisfaction Regional Secretariat of Padang. Keywords : leadership , work motivation , organizational commitment , job satisfaction.